Sub-picosecond ultra-low frequency passively mode-locked fiber laser - Cuadrado Laborde, Christian Ariel (2016)
We developed a nonlinear polarization rotation all-fiber mode-locked erbium-doped fiber laser, with the purpose to reach a sub-picosecond and sub-megahertz light pulse emission. In the process, we observed three different emission regimes as the net birefringence is changed, namely high-power dissipative soliton resonance, low-power soliton regime, and a mixed combination of both. In the pure solitonic regime, a 0.961 MHz train of chirp-free Gaussian pulses was obtained, with a time width of 0.919 ps at 1564.3 nm.